2000
DOI: 10.1093/jn/130.5.1085
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein Expression in Animals: A Physiological Perspective on Function

Abstract: An integration of knowledge concerning regulation of metallothionein expression with research on metallothionein's proposed functions is necessary to delineate how this metalloprotein affects cellular processes, especially zinc metabolism. Metallothionein expression is driven by a number of physiological mediators through several response elements in the metallothionein gene promoter. Cellular accumulation of metallothionein depends on both gene expression and protein degradation. Both depend largely on availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
237
0
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 372 publications
(255 citation statements)
references
References 54 publications
7
237
0
11
Order By: Relevance
“…Another explanation is that zinc may be mobilized from endogenous intracellular zinc-metallothionein by gallium-generated ROS. It is likely that the latter process is at play since others have shown that zinc can be released from metallothionein under conditions of cellular oxidative stress [22,37,38]. Regardless of the process involved, our present study suggests that an increase in the intracellular zinc pool contributes to the upregulation of MT2A expression in cells exposed to gallium nitrate.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Another explanation is that zinc may be mobilized from endogenous intracellular zinc-metallothionein by gallium-generated ROS. It is likely that the latter process is at play since others have shown that zinc can be released from metallothionein under conditions of cellular oxidative stress [22,37,38]. Regardless of the process involved, our present study suggests that an increase in the intracellular zinc pool contributes to the upregulation of MT2A expression in cells exposed to gallium nitrate.…”
Section: Discussionmentioning
confidence: 46%
“…It is known that changes in the cellular zinc pool and oxidative stress may increase MTF-1 activity [22,23] and we therefore hypothesized that gallium might act through these pathways. In the present investigation, we show that the increase in cellular MT2A in cells exposed to gallium nitrate results from a gallium-induced production of reactive oxygen species (ROS) and is associated with a shift in intracellular zinc pools that are accessible to chelation.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] MT is distinctive in having numerous cysteines that participate in metal binding. [12][13][14][15] Part of the normal functioning of MT likely involves zinc homeostasis. 13 MT is also a critical part of the biological response to toxicological stress induced by a variety of metals.…”
mentioning
confidence: 99%
“…4,5,10,11 Metallothionein (MT) is a multi-functional, ubiquitously expressed, low-molecular-weight, metal-binding protein. [12][13][14][15] MT is distinctive in having numerous cysteines that participate in metal binding. [12][13][14][15] Part of the normal functioning of MT likely involves zinc homeostasis.…”
mentioning
confidence: 99%
See 1 more Smart Citation